Influence of crop establishment method and residue management practices on productivity and economics of soybean-based cropping systems: Influence of crop establishment method and residue management practices on productivity and economics of soybean-based cropping systems - R K VERMA; M RAGHAVENDRA; A RAMESH; PRINCE CHOYAL; N KHANDEKAR; M P SHARMA; L S RAJPUT (Journal of Oilseeds Research, 2023)
The field experiment was conducted during kharif, 2021 at ICAR-Indian Institute of Soybean Research, Indore (MP). This experiment was initiated in kharif season of 2017, to study the effect of different cropping systems, crop establishment method and residue management practices on productivity and soil health of soybeanbased cropping systems. Significantly higher yield of soybean was registered under soybean-chickpea. Among the crop establishment techniques, permanent broad bed and furrow (PBBF) + residue retention (R) followed by PBBF + without residue retention (WR) found superior as compared to conventional tillage as per farmer practices. The increase in seed yield was 13.0 to 19.0% under PBBF technology as compared to conventional tillage as per farmers’ practices (CTFP).